Efisiensi Pengiriman Produk ke Warehouse melalui Identifikasi Faktor Keterlambatan Produksi pada PT. Miss Clean Indonesia - Saputra, Danang Adi; Mundari, Siti (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the factors causing delays in product delivery from PT. Miss Clean Indonesia to four main warehouses, which resulted in stock shortages and reduced customer satisfaction. Delivery delays reached 35% in June 2025. The research aims to identify the root causes of these delays and propose improvement strategies using the Fishbone Diagram and Failure Mode and Effect Analysis (FMEA). The Fishbone analysis shows that the primary cause is the misalignment between production scheduling and delivery schedules, while additional issues include limited daily production capacity, machine downtime, and weak coordination between divisions. The FMEA results confirm this finding, with the highest Risk Priority Number (RPN) of 315 assigned to production scheduling failures. To address these problems, a Master Production Schedule (MPS) was developed to synchronize production with warehouse demand. The implementation of the schedule improved delivery accuracy and enhanced overall operational efficiency.